Blind Spot Detection System for Phinisi Ship Navigation Safety: Sistem Deteksi Titik Buta untuk Keselamatan Navigasi Kapal Phinisi - Hanifah Burhanuddin; Akhmad Ahfas (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Maritime tourism development increases the use of large vessels such as phinisi cruise ships which have operational safety challenges. Specific Background The large structure of phinisi ships creates blind spots that can lead to potential collisions with smaller vessels. Knowledge Gap Existing navigation systems have limited capability in detecting objects within blind spot areas in real-time. Aims This study aims to design and implement a blind spot sensing alert system using a laser distance sensor based on Arduino Uno. Results The developed system is capable of detecting object presence within blind spot areas and providing warning signals to assist navigation awareness. Novelty The integration of laser distance sensing with a simple microcontroller-based system provides a practical solution for blind spot monitoring on traditional vessels. Implications This system can support maritime safety by reducing collision risk and can be further developed for wider implementation in similar ship types. Keywords: Blind Spot Detection, Phinisi Ship, Laser Distance Sensor, Arduino Uno, Maritime Safety Key Findings Highlights System identifies object presence in blind navigation areas Warning mechanism supports real-time operator awareness Prototype demonstrates practical implementation on traditional vessel